Modelling of the intralaminar matrix damage with friction effects of fabric reinforced polymers. (15th February 2017) - Treutenaere, S.; Lauro, F.; Bennani, B.; Matsumoto, T.; Mottola, E.
Abstract: Needed to simulate the behaviour of industrial components through finite element analysis, a continuum damage model formulation for fabric reinforced polymers is provided. Based on the Onera Damage Microstructure Model, it considers the influence of privileged direction of intralaminar matrix damage on the stiffness. In this work, the stored strains are considered as representative of the position of the crack lips. Thus, after calculation of the stresses applied to the crack lips, a friction law has been newly implemented in order to represent the hysteresis loops during cyclic loading. Moreover, the possibility of a shear locking, very common among the textile simulations for large shearing, is introduced with its effect on the matrix damage. The present model is applied to simulate various fabric preforms (woven or non-crimp) under cyclic in-plane shear. Because of similarities of the physical phenomena which occur in each investigated materials, the present model is able to represent a realistic behaviour for every preforms investigated.